2015
DOI: 10.1103/physreva.91.023412
|View full text |Cite
|
Sign up to set email alerts
|

Propagating two-particle reduced density matrices without wave functions

Abstract: Describing time-dependent many-body systems where correlation effects play an important role remains a major theoretical challenge. In this paper we develop a time-dependent many-body theory that is based on the two-particle reduced density matrix (2-RDM). We develop a closed equation of motion for the 2-RDM employing a novel reconstruction functional for the three-particle reduced density matrix (3-RDM) that preserves norm, energy, and spin symmetries during time propagation. We show that approximately enforc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 68 publications
3
69
0
Order By: Relevance
“…Implementing a dynamical purification scheme along the lines of that in Ref. that iteratively decreases the magnitude of the negative occupation numbers should be investigated.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…Implementing a dynamical purification scheme along the lines of that in Ref. that iteratively decreases the magnitude of the negative occupation numbers should be investigated.…”
Section: Resultssupporting
confidence: 72%
“…One has then the choice of propagating the equation for ρ 2 alone or propagating it simultaneously alongside the equation for ρ 1 . However, recently it was found that, in the former case, propagating while neglecting the three‐particle correlation term leads to the eventual violation of energy conservation . Now the p ‐RDM can be obtained from higher‐order RDMs via contraction (i.e., partial trace), ρp(x1..xp,x1..xp,t)=1Npdxp+1ρp+1(x1..xp,xp+1,x1..xp,xp+1,t), as follows from the definition Eq.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations